Key Outcomes for a Vocational Rehabilitation Intervention for People With Multiple Sclerosis: A Nominal Group Technique Study - Blanca De Dios Perez; Caolan Senior; Roshan dasNair; Denise Kendrick; Nikos Evangelou; Ian Newsome; Kate Radford (Health Expectations)
ABSTRACT Background Job retention vocational rehabilitation (VR) interventions for people with multiple sclerosis (MS) can positively impact a person's independence and directly influence health and employment outcomes. However, evaluating the effectiveness of VR interventions can be challenging due to their highly individualised nature and the diverse range of potential health and employment outcomes that may be impacted. Aim To identify the most important outcomes of a job retention VR intervention from the perspective of people with MS. Design A nominal group technique (NGT) was conducted with people with MS using Microsoft Teams and Microsoft Forms. The study involved completing a demographic questionnaire, being introduced to VR, silently generating ideas, round‐robin discussions, ranking outcomes and reaching a consensus. NGT data were analysed using thematic analysis. Results We conducted two NGTs involving 10 participants with MS. Nine outcomes were identified and ranked based on priority, relating to four themes: (1) Employer support and collaboration; (2) Empowerment; (3) Symptom management and progression and (4) Professional well‐being and performance. Conclusion Improvements in employer support and symptom management were seen as key outcomes for VR interventions that could eventually lead to enhanced work performance and job retention for people with MS. Future research should explore how feasible it is to collect these outcomes to ascertain the impact of VR on employment over time. Due to the complexity of the outcomes identified, there may be a need to develop new outcome measures with improved validity and sensitivity to these interventions. Patient or Public Contribution This study is part of a larger project co‐developed with three people MS. A lead patient and public involvement representative and lay co‐author reviewed the study topic guide to improve clarity and study focus and supported the group discussions and data analysis with input from the lead researcher.